2019
DOI: 10.33225/pec/19.77.667
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-Efficacy: Effective Indicator Towards Students’ Success in Medium of Education Perspective

Abstract: School is a subculture of any society having different educational diversity. This diversity affects on teachers and students achievements; pillars of teaching learning process. Teachers have great concerns towards students’ success. They deliver plethora of information to improve students’ achievements. Present quantitative ex-post-facto research was framed to explore the effect of teachers’ self-efficacy on students’ achievement scores applying multilingual instructions for students’ success on sample of ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
1
14
0
2
Order By: Relevance
“…Results regarding the second research question showed that teachers' self-efficacy had a significant and positive relationship with learners' l2 achievement. Such a link has been demonstrated through many studies (e.g., Akbari et al, 2008;Good & Brophy, 2003;Hassan, 2019;Mojavezi & Poodineh-Tamiz, 2012). This finding is in line with social cognitive theory that suggests there is a circular relationship between efficacy beliefs and teaching practices (Bandura, 1997).…”
Section: Discussionsupporting
confidence: 78%
“…Results regarding the second research question showed that teachers' self-efficacy had a significant and positive relationship with learners' l2 achievement. Such a link has been demonstrated through many studies (e.g., Akbari et al, 2008;Good & Brophy, 2003;Hassan, 2019;Mojavezi & Poodineh-Tamiz, 2012). This finding is in line with social cognitive theory that suggests there is a circular relationship between efficacy beliefs and teaching practices (Bandura, 1997).…”
Section: Discussionsupporting
confidence: 78%
“…It is evident that Pakistani students enrolled in public and private universities are facing problems of regularly shifting of cultural diversity, language dilemma, teachers' technological skills, weak media-structured classrooms, poor technological literacy knowledge and facing poor vibrant learning environment (Gopang et al, 2016;Govt. of Pakistan, 2013;Hassan, 2019;Hassan & Akbar, 2016;Rahman, 2004;Saleem et al, 2019;Yousaf & Dahmani, 2008). Furthermore, there is lack of policymakers' cooperation, poor application of curriculum based technological literacy skilled staff, less structuring of technological and physical facilities and educational infrastructure (Ameen, 2007;Batool & Qureshi, 2007;Govt.…”
Section: Problem Statementmentioning
confidence: 99%
“…Self-efficacy is a critical cognitive trait that significantly impacts goal achievement. Teachers with higher education are more effective in helping pupils reach their goals (Hassan, 2019;Pell, Iqbal, & Sohail, 2010;Shaukat, 2011). Further, in a contentious medium of education approaches, teachers' self-efficacy is considered a fundamental construct that determines students' accomplishment scores.…”
Section: Teachers' Self-efficacymentioning
confidence: 99%